Key Questions in Marine Megafauna Movement Ecology. (June 2016) - Hays, Graeme C.; Ferreira, Luciana C.; Sequeira, Ana M.M.; Meekan, Mark G.; Duarte, Carlos M.; Bailey, Helen; Bailleul, Fred; Bowen, W. Don; Caley, M. Julian; Costa, Daniel P.; Eguíluz, Victor M.; Fossette, Sabrina; et al.
Abstract : It is a golden age for animal movement studies and so an opportune time to assess priorities for future work. We assembled 40 experts to identify key questions in this field, focussing on marine megafauna, which include a broad range of birds, mammals, reptiles, and fish. Research on these taxa has both underpinned many of the recent technical developments and led to fundamental discoveries in the field. We show that the questions have broad applicability to other taxa, including terrestrial animals, flying insects, and swimming invertebrates, and, as such, this exercise provides a useful roadmap for targeted deployments and data syntheses that should advance the field of movement ecology. Trends: Technical advances make this an exciting time for animal movement studies, with a range of small, reliable data-loggers and transmitters that can record horizontal and vertical movements as well as aspects of physiology and reproductive biology. Forty experts identified key questions in the field of movement ecology. Questions have broad applicability across species, habitats, and spatial scales, and apply to animals in both marine and terrestrial habitats as well as both vertebrates and invertebrates, including birds, mammals, reptiles, fish, insects, and plankton.